Communicating international politics narratives of security, democracy and human rights in contemporary society: indexing and analysis using online monitoring data - Olimid, Anca Parmena; Georgescu, Cătălina Maria; Gherghe, Cosmin Lucian (Frontiers in Sociology, 2024)
ObjectivesThe role of the current research is to set up a conceptual and analytical framework of the security, democracy and human rights linkage in contemporary society mainly based on the indexing, monitoring and research of online content for the period 1945–2019.Methods and methodologyDue to the focused timeline outlining the scientific research for the period 1945–2019, the paper favors both quantitative and qualitative approaches that follow a systemic framework of several thematic clusters which act as supporting pillars of analytical research by using Google Ngrams: (a) norms and constitutional values and principles; (b) civil and legal liberties; (c) human and individual approaches; (d) institutional governance and organizational establishment; (e) freedoms, civil and political rights.Results and discussionsThe research results explore the variations in the frequency of appearances of the selected concepts in the specialized literature indexed by the Google platform indicating essential aspects of the conceptual and theoretical evolutions in strict dependence to the significant resolutions of the Security Council of the United Nations adopted in the same period and focusing on three central concepts: security, democracy and human rights. The spectrum of research singles out fifteen figures and an integrated analysis of contextual, historical, political, institutional, legal and social factors.ConclusionThe research aims to expand the field of reference and analysis of the three notions of security, democracy and human rights by integrating the multifactorial and multi-conditional analysis for the interpretation of the results of the fifteen figures. In the broader framework of online monitoring and complementarily with the spectrum of UNSC resolutions, the research will use contemporary topics, intensely debated, used and monitored, focusing on the conceptual and linguistic study and on the relationship between the analytical inventory of scientific research and the international decision-making spectrum. This relationship is mediated by the lexicon of politics and the sociology of international relations, which reflected a growing evolutionary linguistic semantics since 1945, the year of the establishment of the United Nations.